2020
DOI: 10.3102/0162373720949513
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between School Turnaround and Student Outcomes: A Meta-Analysis

Abstract: School turnaround has emerged as a predominant strategy to improve chronically low-performing schools, although the approach remains controversial. This meta-analysis synthesizes results from 35 studies to examine the relationship between school turnaround and various student outcomes. We find that school turnaround is associated with improved attendance, standardized test scores, and graduation rates. When separating the results by the different turnaround models, transformation, turnaround, and restart model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
0
20
0
2
Order By: Relevance
“…The intentional replacement of ineffective principals in the first year of school reform has been a prominent component in the theory of change for school turnaround (Kutash et al, 2010;Redding & Nguyen, 2020;Zimmer et al, 2017). This approach has been grounded in evidence that school leaders are instrumental for student achievement (Leithwood et al, 2004).…”
Section: Principal Turnover and Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…The intentional replacement of ineffective principals in the first year of school reform has been a prominent component in the theory of change for school turnaround (Kutash et al, 2010;Redding & Nguyen, 2020;Zimmer et al, 2017). This approach has been grounded in evidence that school leaders are instrumental for student achievement (Leithwood et al, 2004).…”
Section: Principal Turnover and Effectivenessmentioning
confidence: 99%
“…On average, school turnaround has shown little evidence of producing sustained school improvement (Dragoset et al, 2016, 2017; Pham et al, 2020). Furthermore, research finds that different approaches to school turnaround vary in their effectiveness (Redding & Nguyen, 2020; Schueler et al, 2020). For example, one set of studies found that a turnaround model maintaining local governance with increased autonomy outperformed a state takeover model in which school management was largely turned over to charter management organizations (CMOs) (Henry et al, 2020, Pham et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mediados de los años 90 en Texas, las escuelas comenzaron a ser clasificadas como "ejemplares", "reconocidas", "aceptables" o "de bajo rendimiento", y en Florida, se les asignó una letra desde la "A" a la "F", simulando el sistema de calificaciones en exámenes de estudiantes. Estas clasificaciones en varios estados no traían acarreadas sanciones o premios directos para las escuelas (SAW et al, 2017;HOWE;MURRAY, 2015).…”
Section: Marco Teóricounclassified
“…Además, a nivel federal las escuelas fueron diferenciadas entre aquellas que logran un "progreso anual adecuado" (Made AYP 2 ) y quienes "no logran progreso anual adecuado" (No-made AYP). Las escuelas que no logran los avances esperados durante dos o más años pueden recibir sanciones, tales como el ofrecimiento por parte del estado de una nueva escuela para sus estudiantes, incluyendo la subvención del transporte (SAW et al, 2017).…”
Section: Marco Teóricounclassified